Clinical manifestations and cross-reactions between cockroaches and termites and identification of termites’ major allergens - Mey-Fann Lee; Chi-Shen Wu; Tzu-Mei Lin; Hou-Feng Li; Yi-Hsing Chen (PLoS ONE, 2026)
The American cockroach ( Periplaneta Americana, CRa A) is a strong risk factor for allergic sensitization and asthma morbidity. Molecular phylogenetic studies demonstrated termites are social cockroaches specialized in feeding on plant materials. We hypothesized that termite allergies may be misdiagnosed as cockroach allergies due to cross-reactivity in routine clinical tests. Herein, we identified the allergenic cross-reaction between CRa A and termites and determined the clinical significance of termite allergies. Sixteen subjects with a history of exposure to termites, nine (56%) had a positive immediate skin reaction to Coptotermes formosanus or Coptotermes gestroi , but only two individuals were reactive to CRa A. Among the termite-allergic subjects, 8 had rhinitis and one had dermatitis, which manifested as itchy eczematous skin rashes. Immunoblotting revealed 7 allergenic components could bind specific IgE antibodies in 8 termite-allergic patients. The major allergens of 30/32-, 43-, and 70-kDa were Copt f 7, Copt f 9, and Copt f 3 by immunoblot inhibitions. Antibodies against Per a 3, Per a 4, and Per a 6 recognized bands in both extracts of cockroach and alate termites, indicating a more similar gene expression between alate termites and cockroaches compared to worker and soldier castes. Our study underscores the importance of recognizing termites as a novel indoor allergenic source and the necessity for further research to develop effective diagnostic and therapeutic strategies.